The Legal Consequences of the Cancellation of Peace Agreements in PKPU for Secured Creditors: A Case Study of the Jakarta Central District Court - Webi Achmad, Rivaldi; Bernad Nainggolan; Fernando Silalahi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The Indonesian Suspension of Debt Payment Obligations (PKPU) framework, designed to prevent bankruptcy and provide debt restructuring opportunities, faces significant challenges, particularly in enforcing peace agreements post-homologation. This study investigates the legal implications of these challenges, with a focus on creditors’ rights, particularly for separatist creditors holding security interests. The research aims to identify the procedural and legal gaps that hinder the effective enforcement of peace agreements and propose recommendations for improving the PKPU system. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and document analysis, focusing on judicial practices, legal interpretations, and the experiences of creditors and debtors involved in the PKPU process. The findings reveal critical issues such as the lack of a coercive enforcement mechanism, judicial inconsistencies, and the legal ambiguity surrounding the remedies available to creditors when debtors breach peace agreements. The study highlights the need for a more structured enforcement process, clearer guidelines for creditor rights, and enhanced legal protections for secured creditors. Policy recommendations include introducing automatic enforcement mechanisms, refining judicial procedures, and improving creditor participation in the debt restructuring process to ensure greater legal certainty and fairness..".